Economic evaluation of dabigatran etexilate for the prevention of venous thromboembolism in patients aged over 75 years or with moderate renal impairment undergoing total knee or hip replacement - Wolowacz, Sorrel E.; Roskell, Neil S.; Plumb, Jonathan M.; Clemens, Andreas; Noack, Herbert; Robinson, Paul A.; Dolan, Gerry; Brenkel, Ivan J. (Thrombosis and Haemostasis, 2010)
Oral dabigatran etexilate is indicated for the prevention of venous thromboembolism (VTE) in patients undergoing total knee replacement or total hip replacement. We investigated the cost-effectiveness of the 150 mg once daily (od) dose recommended for patients aged over 75 or with moderate renal impairment, from a United Kingdom National Health Service perspective. Dabigatran etexilate was compared with subcutaneous enoxaparin 40 mg od, using a decision model. Risks for VTE and bleeding were derived from subgroup analyses of the phase III trials. Dabigatran etexilate was less costly than enoxaparin; cost savings varied from £62 to £274 (base-case analyses) and were primarily due to differences in administration costs. Results were robust across a range of sensitivity analyses. Dabigatran etexilate 150 mg od is cost saving compared with enoxaparin 40 mg od in patients aged over 75 years and in patients with moderate renal impairment, with comparable efficacy and safety.
Keywords: Thromboembolism; primary prevention; total hip replacement; total knee replacement; economics